Anti-melanogenesis and anti-tyrosinase properties of Pistacia atlantica subsp. mutica extracts on B16F10 murine melanoma cells - Samira Eghbali-Feriz; Akram Taleghani; Hadi Al-Najjar; Seyed Ahmad Emami; Homa Rahimi; Javad Asili; Samira Hasanzadeh; Zahra Tayarani-Najaran (Wolters Kluwer Medknow Publications, 2018)
Pistacia atlantica (P. atlantica) subsp. mutica has been used in traditional medicine and is famous for its medicinal properties. The aim of this study was to evaluate the effect of methanol (MeOH), n-hexane, dichloromethane (CH2Cl2), n-butanol (BuOH), ethyl acetate (EtOAc), water extracts and essential oil of P. atlantica subsp. mutica on melanin synthesis and oxidative stress in B16F10 melanoma cell line. The B16F10 cells viability after treatment with increasing concentrations of different extracts of the plant (0.2-200 μg/mL) was measured using resazurin. Essential oil composition was identified by gas-chromatography-mass spectrometry (GC-MS) analysis and inhibitory effect on synthesis of melanin, mushroom tyrosinase activity, cellular tyrosinase, and oxidative stress were evaluated by the colorimetric and fluorometric methods. The data showed extracts at concentrations 0.2-200 μg/mL, did not show significant toxicity on melanoma cells but concentrations of 200 μg/mL of essential oil had cytotoxic effect. Pistacia atlantica subsp. mutica could inhibit the mushroom tyrosinase activity. Also the amount of melanin in B16F10 cells declined. In addition, the ability of P. atlantica subsp. mutica extracts in decreasing the amount of reactive oxygen species in melanoma cells revealed remarkable antioxidant activity. In addition, all concentrations of essential oil had no significant effect in this study. The melanogenesis inhibitory and antioxidant effects of P. atlantica subsp. mutica on B16F10 cells may suggest the potential whitening activity of the plant for using in dermatological skin care products and for prevention of skin aging in cosmetic industry.